Preliminary Predictors of Initial Attendance, Symptom Burden, and Motor Subtype in a US Functional Neurological Disorders Clinic Population. Issue 4 (December 2016) - Perez, David L.; Young, Sigrid S.; King, Julie N.; Guarino, Anthony J.; Dworetzky, Barbara A.; Flaherty, Alice; Chemali, Zeina; Caplan, David; Dickerson, Bradford C.
Abstract : Background and Objective: Although many patients present with functional neurological symptoms (FNS), few US clinics offer specialized FNS care, and data on clinic attendees remain limited. We determined predictors of initial attendance, symptom burden, and FNS subtype in the first patients referred to our Functional Neurological Disorders Clinic for suspected FNS. Methods: We reviewed the charts of 62 consecutive patients (46 women, 16 men). Regression analyses investigated predictors of keeping the first scheduled clinic appointment. For the 49 patients who did keep that appointment, regression analyses examined neuropsychiatric factors associated with symptom burden and motor FNS subtypes. Results: The odds of not keeping the first appointment were 10.4 times greater for patients referred from the emergency department than from other sources. The patients who kept their appointment reported a symptom burden that was significantly associated with a past FNS-related emergency department visit and a diagnosis of another medically unexplained somatic syndrome. The number of FNS findings on neurological examination also correlated with a history of an FNS-related emergency department visit. Patients with psychogenic non-epileptic seizures reported cognitive complaints and prior psychiatric hospitalizations significantly more often than did patients with other FNS. One fourth of all patients had two or more motor FNS. Conclusions: In our FNS cohort, patients were less likely to keep an initial clinic appointment if they were referred from the emergency department than from other sources. Patients with psychogenic non-epileptic seizures were more likely to report cognitive symptoms and past psychiatric hospitalizations than patients with other FNS.